Examining Teacher Opinions of Age and Duration of English Language Support in International Schools - Lehman, Clayton (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
International school educators hold various opinions about language acquisition. These opinions are often formed during their training and previous teaching experiences in their home countries. This quantitative cross-sectional survey-based study explored and compared the opinions of 283 English as a Foreign Language (EFL), Primary, and Secondary English teachers in international schools in Africa, Asia, the Middle East, and South America. The study examined the age EFL students should begin receiving EFL teacher support and for how long. The study revealed statistically significant differences between EFL and Primary teachers concerning the age for EFL students to begin receiving support from an EFL teacher. Further revealed were significant differences between EFL and Secondary English teachers concerning the duration of EFL support. Overall, participants' opinions about the duration of EFL support are well below previously reported data, which is troubling since EFL students in English-medium international schools are learning English for academic purposes.